-8x-3x-11=-8+7

Simple and best practice solution for -8x-3x-11=-8+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x-3x-11=-8+7 equation:


Simplifying
-8x + -3x + -11 = -8 + 7

Reorder the terms:
-11 + -8x + -3x = -8 + 7

Combine like terms: -8x + -3x = -11x
-11 + -11x = -8 + 7

Combine like terms: -8 + 7 = -1
-11 + -11x = -1

Solving
-11 + -11x = -1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + -11x = -1 + 11

Combine like terms: -11 + 11 = 0
0 + -11x = -1 + 11
-11x = -1 + 11

Combine like terms: -1 + 11 = 10
-11x = 10

Divide each side by '-11'.
x = -0.9090909091

Simplifying
x = -0.9090909091

See similar equations:

| 99=5n+9 | | 4(3x-5)+12(x-5)=70 | | 6-6(5+5m)=-24+8m | | X^2+5x+7=49 | | X^2+5x+58=0 | | R^3-r^2-4r+4=0 | | log(6x+8)=log(12) | | -7(8k-8)=-392 | | 720/6 | | 3cos^2x=2 | | 6tons=Pounds | | 720/3 | | Y=-1/2(x-6)(x8) | | 2(3x+2)=4(2x-5) | | 8s-26+5s-15=180 | | 6b+4b=-12+8b | | 25*7+11*3+2*3= | | 2x^2+-8x-384=0 | | 2(x+2)=-2(x+6) | | 44=x(5+6) | | 7x-(2x+5)=36 | | 2w-36=w-12 | | 46*7+87*3+21*3= | | W-12=2w-36 | | 1/3✖️3/4 | | 1/3✖️3/4=3/8 | | 29*7+16*3+8*3= | | 6y-14=9y-5 | | -3(y+2)=7y-8+4(2y+4) | | .027+2-.035x=0 | | 540*10+160*3= | | 3s-36=5s-88 |

Equations solver categories